ANALYSIS OF THE ROLE OF UMKM IN INCREASING COMMUNITY INCOME IN BINJAI CITY - Zasfayyard, Hafiz (Proceeding International Seminar of Islamic Studies, 2024)
MSMEs have a very important role in national and regional economic development. The big opportunities that the MSME sector has are said to be very large and MSMEs are able to survive the crisis. The lack of attention that MSMEs receive in Indonesia has brought down many large businesses, but the majority of MSMEs continue to survive, in fact their numbers are increasing very rapidly. MSMEs are also the backbone of the people's economy which is able to eradicate poverty and absorb labor. MSMEs also create jobs faster than other business sectors, and MSMEs also make an important contribution to exports and trade. . The aim of this research is to determine and analyze the role of MSMEs in increasing income and economic growth in Binjai City . The type of data in this research is quantitative data with secondary data sources. The data collection technique used is observation and descriptive analysis techniques. The results of this research are that currently the total number of MSMEs in Binjai City is 20,852 MSMEs. MSMEs have the potential for a strong economic base because the number of MSMEs is very large and the labor absorption capacity is very large. Binjai City MSMEs have not been able to increase the regional income of Binjai City, because community income as seen from public expenditure per capita is still low